Business, victimisation and victimology: Reflections on contemporary patterns of commercial victimisation and the concept of businesses as 'ideal victims'. (May 2016) - Hopkins, Matt
The recent publication of the first English/Welsh Commercial Victimisation Survey (CVS) in over 10 years represents a good time to consider both 'crimes against businesses' and the place of commercial victims within the discipline of victimology. While some research points to high crime rates against the commercial sector, it has been argued that the abstract concept of 'crimes against businesses' has been used by government and businesses to construct a notion of business victimhood in order to place businesses at the centre of policy concerning crime prevention. Critics suggest this recognition of the 'business as a victim' not only moves attention away from the illegal behaviours of businesses (businesses as victimisers), but also it gives corporations that can already absorb crime costs the power to dominate debates around law, order and crime prevention. Using data from the CVS, patterns of crimes against business are outlined and some of the main characteristics of victims are identified. Consideration is then given to what these data mean in relation to the concept of businesses as victims. Using Christie's notion of the ideal victim as a heuristic device, it is explored whether businesses can ever be viewed as 'ideal' victims and why achieving victim status might be important. Finally, some fruitful areas for further research are considered.